WASTE BANK FROM AN ISLAMIC ECONOMIC PERSPECTIVE (CASE STUDY AT BANK SAMPAH SEJAHTERA) - Bismantara Bismantara; Muhamad Rijal; Dilla Nur Fauziah (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
This waste problem occurs not only because of the government's lack of attention but more than that is the awareness of the community itself. The problem of waste has raised public awareness to take part in managing waste. Namely the Garbage Bank. The formulation of the problem that the author wants to examine is analyzed by the principles of Islamic economics on community economic empowerment through the management of the Prosperous Garbage Bank in Sirap Village, Tanjungsiang District. From the results of the research, Islamic economic principles that are relevant to community empowerment through waste banks are the principle of justice, where people have an appropriate and clear price for the waste they save, then the principle of equality, where it does not matter which customer is more prioritized at Bank Sejahtera, then the principle of helping, with the waste bank, inorganic waste that cannot be decomposed and destroys nature can be recycled so that it has more added value for the waste bank customer, then the principle of participation, there are no restrictions on age, gender, status when you will become a bank customer rubbish.